2021
DOI: 10.1155/2021/9916461
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Satellite Operation Prediction Using a BiLSTM Deep Learning Model

Abstract: The current satellite management system mainly relies on manual work. If small faults cannot be found in time, it may cause systematic fault problems and then affect the accuracy of satellite data and the service quality of meteorological satellite. If the operation trend of satellite will be predicted, the fault can be avoided. However, the satellite system is complex, and the telemetry signal is unstable, nonlinear, and time-related. It is difficult to predict through a certain model. Based on these, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…• In Peng et al 41 a comparison between BiLSTM, LSTM and RNN models is shown, the resultant RMSE score values of the BiLSTM model are consistently smaller than those of LSTM and RNN, leading to the conclusion that the BiLSTM model can predict the operation trends of a meteorological satellite with greater effectiveness.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…• In Peng et al 41 a comparison between BiLSTM, LSTM and RNN models is shown, the resultant RMSE score values of the BiLSTM model are consistently smaller than those of LSTM and RNN, leading to the conclusion that the BiLSTM model can predict the operation trends of a meteorological satellite with greater effectiveness.…”
Section: Referencesmentioning
confidence: 99%
“…The given factors first indivialually then in combinations using a sliding window technique for leak classification. The precision, recall and accuracy was measured to be 86%, 86%, and 85%, respectively. In Peng et al 41 a comparison between BiLSTM, LSTM and RNN models is shown, the resultant RMSE score values of the BiLSTM model are consistently smaller than those of LSTM and RNN, leading to the conclusion that the BiLSTM model can predict the operation trends of a meteorological satellite with greater effectiveness.…”
Section: Applicationsmentioning
confidence: 99%
“…Notwithstanding, price data is not only dependent on information from the past, but also related to future financial conditions. BiLSTM is the expansion of LSTM that combines the forward and backward processing to capture useful information [25,26]. Hence, it can be performed to make the forecast more precise.…”
Section: Bilstmmentioning
confidence: 99%
“…The BiLSTM [34] network is a two-layer LSTM network consisting of a combination of forward and reverse LSTM layers. The network structure of the BiLSTM is shown in Figure 4.…”
Section: Bilstm Networkmentioning
confidence: 99%